2020
DOI: 10.1039/c9bm01171d
|View full text |Cite
|
Sign up to set email alerts
|

CD44 targeted redox-triggered self-assembly with magnetic enhanced EPR effects for effective amplification of gambogic acid to treat triple-negative breast cancer

Abstract: Scheme of mPEG-HA/CSO-SS-Hex/SPION/GA self-assembly preparation and the magnetism-enhanced EPR in vivo and in vitro trafficking pathways of the polymeric self-assembly.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(24 citation statements)
references
References 37 publications
0
24
0
Order By: Relevance
“…Sang and coworkers produced polymeric micelles that contained iron oxide nanoparticles and were functionalized with hyaluronic acid (which can target the CD44 receptor). After application of the magnetic field, these particles exhibited significantly stronger affinity and intercellular penetration of 4T1 cancer cells than the control [58]. Effective targeting was also observed during in vivo imaging of tumorbearing mice after intravenous injection of these magnetic nanoparticles and exposure to a magnetic field [58].…”
Section: Discussionmentioning
confidence: 79%
“…Sang and coworkers produced polymeric micelles that contained iron oxide nanoparticles and were functionalized with hyaluronic acid (which can target the CD44 receptor). After application of the magnetic field, these particles exhibited significantly stronger affinity and intercellular penetration of 4T1 cancer cells than the control [58]. Effective targeting was also observed during in vivo imaging of tumorbearing mice after intravenous injection of these magnetic nanoparticles and exposure to a magnetic field [58].…”
Section: Discussionmentioning
confidence: 79%
“…Sang et al developed a GA drug nanoconjugate with an outer layer made up of mono-aminated poly (ethylene glycol)-grafted hyaluronic acid that can specifically target CD44 receptors on TNBC (Hyaluronic acid has higher affinity to bind CD44 on TNBC); the middle layer comprises disulfide-linked hexadecanol (Hex) as well as chitosan oligosaccharide (CSO) that controls the drug release, while the core layer is made up of SPIONs attached to GA that can increase the enhanced permeation and retention effect due to magnetic focusing. This complex of mPEG-HA/CSO-SS-Hex/SPION/GA nanosystem led to efficient delivery of the drug using magnetic guidance to focus in TNBC microenvironment [200].…”
Section: (I) Quantum Dots (Qd)mentioning
confidence: 99%
“…To improve the targetability of NP-loaded drug complexes, Seng et al reported dualtargeted redox-responsive hybrid polymeric micelles functionalized with HA to improve the delivery efficiency of an NP-loaded anticancer drug, Gambogic acid (GA) [135]. A self-assembled nanosystem composed of an outer layer of PEGylated HA for targeting the CD-44 receptor, reduction-responsive disulfide-linked hexadecanol (HEX), chitosan (CHO), and superparamagnetic iron oxide nanoparticles (SPION) as a core to load GA.…”
Section: Cd-44 Targeted Drug-loaded Npsmentioning
confidence: 99%
“…There was a 88% reduction in the tumor volume for mPEG-HA/CHO-SS-HEX-SPION-GA with MF compared to free GA formulations. A biodistribution and toxicity study with the nano-formulation revealed extended concentrations of the drug in plasma without any notable toxicity [135].…”
Section: Cd-44 Targeted Drug-loaded Npsmentioning
confidence: 99%